Studies in Gnosticism and Alexandrian Christianity - Broek, Roelof van den, (Nag Hammadi and Manichaean Studies ;, 1996)
The discovery of the Nag Hammadi Library (1945) has given an enormous impetus not only to the study of ancient Gnosticism but also to that of early Christianity in general. Most of the studies contained in this volume deal with mythological conceptions and theological ideas found in various Nag Hammadi writings. The gnostic views on the nature of God and on creation and salvation receive particular attention, ranging from Philo to the medieval Cathars. The Nag Hammadi Library also shed new light on the development of early Alexandrian Christianity and its theology. The book contains six studies which explicitly deal with these topics. This volume is of interest to students of Gnosticism, early Christianity and Graeco-Roman religious and philosophical ideas in general.